The The effect of iron on precipitation hardening in the Cu-Ni-Mn alloys - Sukhova, O.V. (Physics and Chemistry of Solid State, 2021)
The peculiarities in the structure and properties formation of precipitation-hardened Сu–Ni–Mn–Fe alloys within the concentration range of Ni (19.3–21.0 %), Mn (19.5–20.5 %), Fe (0.6–2.7 %), Cu – balance (in wt. %) were investigated in this work. The methods of quantitative metallography, X-ray analysis, scanning electron microscopy, energy-dispersive spectroscopy and differential thermal analysis were applied. Two solid solutions based on a-Cu differing in composition and hardness were found in the structure of the cast Сu–Ni–Mn–Fe alloys. The temperature ranges of solutions’ formation were determined as (1010±10) °С and (890±10) °С, correspondingly. NiMn phase was also formed at (405±15) °С due to precipitation hardening. In the Сu–Ni–Mn–Fe alloys annealed at 500 and 900 °С for 60–750 hours, the volume fraction and size of NiMn precipitates increased with prolonging annealing time and lowering annealing temperature. As iron content was raised up to 2.7 wt. %, the density of NiMn precipitates increased, especially during first 60 hours of annealing at 900 °С. By adding iron, oxidation resistance was improved, but melting temperature and fluidity did not yield any significant change. Hardness of the Сu–Ni–Mn–Fe alloys with higher iron contents increased by 10 НRB on average. However, when test temperature was raised up to 400 °С, tensile strength decreased (by 1.3 times) and elongation dropped markedly (by 10 times).